2022
DOI: 10.1111/1471-0307.12857
|View full text |Cite
|
Sign up to set email alerts
|

Effect of total and differential somatic cell count on yield, composition and predicted coagulation properties from individual dairy cows

Abstract: This study aimed to investigate the effect of interaction between total (SCC) and differential somatic cell count (DSCC) on milk yield, composition and coagulation traits from individual dairy cows. A total of 159 224 test-day records (daily milk yield, composition and coagulation traits) have been collected during a period of 14 months from 12 849 Holstein-Friesian and 9275 Simmental cows farmed in 223 herds. The interaction between somatic cell traits was highly significant for almost all the evaluated trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
0
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
2
1
0
3
Order By: Relevance
“…For the reason explained above, the casein index was expected to be the lowest in UHS4. This agrees with Mariani et al [ 32 ] who observed the lowest casein index in cows with simultaneously high SCC and low DSCC.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For the reason explained above, the casein index was expected to be the lowest in UHS4. This agrees with Mariani et al [ 32 ] who observed the lowest casein index in cows with simultaneously high SCC and low DSCC.…”
Section: Discussionsupporting
confidence: 93%
“…Milk urea concentration was the lowest in UHS3 group. This is, at least partly, in line with Mariani et al [ 32 ] who observed a lower concentration of urea in milk of Holstein-Friesian and Simmental cows that presented high values for both DSCC and SCC. Pegolo et al [ 36 ] did not report significant associations between milk urea and SCC at different levels of DSCC in Holstein Friesians.…”
Section: Discussionsupporting
confidence: 90%
“…Problémy vemena sa prejavujú zmenami v jeho štruktúre a funkcii; majú za následok zmeny v množstve vydojeného mlieka i v jeho zložení (Rajčevič et al, 2003). Náklady na výrobu mlieka rastú z roka na rok (aj v súvislosti s riešením zdravotných problémov), preto je potrebné, aby mali chovatelia k dispozícii postupy, ktoré im pomôžu vyrovnať sa s touto situáciou (Mariani et al, 2022). Nižšia kvalita mlieka má vplyv na ekonomickú efektívnosť chovu.…”
Section: Marta Oravcová Maroš čObirka Vladimír Tančin Lucia Mačuhová ...unclassified
“…Pri produkcii mlieka a obsahu laktózy (v oboch analýzach) sa potvrdila negatívna závislosť, t. j. s rastúcim PSB sa znižoval denný nádoj a obsah laktózy. Podobné zistenia publikovali El-Tahawy a El-Fa (2010), Kul et al, (2019), Mariani et al, (2022). Za príčinu tohto javu možno podľa Bezmana et al, (2015) a Bobba et al, (2017) považovať prítomnosť patogénov v mlieku.…”
Section: Tabuľka 1 Analýza Rozptylu (Model Pre 1 Laktáciu 1)unclassified
See 1 more Smart Citation